La filosofía trascendental de Kant y la cuestión del escepticismo - Piulats Riu, Octavi (THÉMATA. Revista de Filosofía, 2012)
Uno de los grandes momentos de la Historia de la Filosofía se centra en el debate que Immanuel Kant llevó a término contra el escepticismo moderno. El presente artículo reconstruye, a través del concepto kantiano de “experiencia”, las estrategias que el filósofo de Könisberg utiliza contra el escepticismo. El resultado de la investigación muestra como todo el edificio gnoseológico kantiano, incluyendo su famosa división entre “fenómeno” y “noumeno”, se halla mediatizado por este intento de superación del escepticismo. One of the greatest events in the History of the Philosophy is without doubt the systematic debate that Immanuel Kant is leading against modern Scepticism. The main purpose of this article is to demonstrate that his famous division between “phainoma” and “noumena” is totally influenced by the force of the intellectual fight of Kant against Scepticism. This investigation concerns about all the reconstruction of the concept of “experience” in the way that Kant expose it in his main works. Key words: Kant, Scepticism, tropoi, dialectic, antinomy, meaning and signification.